Władysława Witwickiego psychologia zaprzepaszczonych szans - Rzepa, Teresa (Filozofia Nauki, 1999)
Many years I have spent exploring the psychological work of Wladyslaw Witwicki authorize me to utter a general verdict, contained in the title phrase „psychology of missed opportunities”. In the article I present arguments for this diagnosis, looking for the origins and results of „Witwicki syndrome”, which may be helpful in diagnosing other scientists' productions. The essence of that syndrome consists in: first, thinking of numerous and original ideas and visions of achieving them; then, making a weakly justified choice from among them - and, finally, stubbornly arguing that the chosen solution to the problem is the only permissible. I illustrate the symptoms of the characterized syndrome with the examples taken from the range of Wladyslaw Witwicki's proposals, both theoretical and methodological.